Umbilical infections in foals: microbiological investigation and management. (3rd June 2017) - Rampacci, E.; Passamonti, F.; Bottinelli, M.; Stefanetti, V.; Cercone, M.; Nannarone, S.; Gialletti, R.; Beccati, F.; Coletti, M.; Pepe, M.
Abstract : This study aims to investigate the bacteria involved in equine omphalitis and their susceptibility to antimicrobial drugs, and consequently to provide guidelines concerning the most suitable treatment protocol in accordance with the clinical, ultrasound and laboratory findings. Forty foals aged between one and 30 days were evaluated in the course of this investigation. An ultrasound examination of all umbilical remnants was carried out carefully in all foals; umbilical swabs were collected for bacteriological examination, and blood samples were collected for blood culture from 19 foals with fever and abnormal blood values. Bacterial omphalitis was observed in 95 per cent of foals and bacterial septicaemia was diagnosed in 11 cases. Enterobacteria and coccoid Gram‐positive bacteria were isolated more frequently than Serratia marcescens, Pantoea agglomerans and Trueperella pyogenes . Omphalectomy was performed in 77.5 per cent of the foals examined; the remainder were treated only medically with antimicrobial drugs as recommended by antibiotic susceptibility testing performed for all bacteria isolated. Antibiotic therapy was successful in all foals that only received medical treatment; nevertheless, omphalectomy was performed in most cases particularly in situations of clinical decline despite antibiotic therapy and when involvement of umbilical vein, fever and joint disorders were observed.